Cotidiano de adolescentes vinculados a um Centro de Atenção Psicossocial Infantojuvenil (CAPSi): realidade e perspectivas - Fernandes, Amanda Dourado Souza Akahosi (2014)
The development consists in a reciprocal interaction process, between the person and its context through time. Under this perspective, the psychic suffering during adolescence will impact the development of teenagers as well as impact those with whom they coexist. To comprehend the quotidian life and the activities of teenagers who are in psychic suffering is important for the identification of processes that this suffering creates in their daily lives and for the possibility of intervention towards these teens. The objective of the present study is to understand the quotidian life of teenagers who are in psychic suffering and linked to a Center of Psychosocial Attention to Child-Youth (CAPSi). It is an exploratory study, descriptive, of qualitative approach, done though the research methodology based on the ecological insertion. Thirteen teenagers between the ages of 12 and 18, each one linked to a CAPSi of a big city in the state of SP, as well as fifteen people of their social support network, participated of the research. The participants concerning the social support network were nominated by the teenagers themselves and among them were CAPSi technicians, family members and friends. The used instruments for data collection were two semi-structured interview scripts and the field journal. In order to analyze the data, the researcher executed repeatedly measures and identified representative fragments of the observed reality. In concerns of the interview analyzes, the Collective Subject Discourse technique was applied. The results indicate a quotidian life of limited activities, school dropout, impossibility to have recreational activities, difficulty when it comes to the relationship with family member and social relations practically restricted to the CAPSi context. It s discussed that the relations established between the teenagers and the diversified contexts of pertinent development to this stage of their lives do not occur in a effective way, while the mutuality concerning interpersonal relations are not part of these teenagers reality and their insertion on social places as well as opportunity of learning are limited. It is considered that from the quotidian life recognition of those teenagers under psychic suffering, the present fragmentations were evidenced, that shall be examined and considered in the creation of public policies, and the reach, as well as the limits, of the existent strategies are questioned.